Armenia : Strategic Mineral Sector Sustainability Assessment - World Bank (World Bank, Washington, DC, 2016)
This report provides a review of the Armenian mining sector, and assesses its potential to contribute to sustainable economic growth and development. Based on the findings, it provides recommendations for initiatives and actions for the future development of the sector. The report was produced in the period October 2015 to April 2016. It was commissioned by the World Bank with the aim to assist the Armenian government to gain a better understanding of key social and environmental challenges and future opportunities for the Armenian Mining Sector; and to support the development of a minerals strategy which is line with international good practices and which contributes to sustainable development. The findings are based on: desktop reviews of existing documents; a large number of meetings and interviews with affected and interested stakeholders; field work performed in the main mining districts of Armenia; stakeholder workshops. Comments, suggestions and corrections on a draft version of this report has been provided by representatives of the GoA, and the World Bank. Further, oversight and feedback was continuously provided by representatives of the World Bank.